The Effect of an Educational Program based on Health Literacy Strategies on Physical Activity in Postpartum Women - Monireh Abdollahi; Nooshin Peyman (Mashhad University of Medical Sciences, 2017)
Background & aim: Health literacy is the degree to which individuals can obtain, process, and understand the required basic health information and services to enhance and sustain good health status. Mothers with higher health literacy may have more physical activity than others in the postpartum period. This study sought to assess the effect of an educational program based on health literacy strategies on promoting physical activity in postpartum women. Methods: This quasi-experimental study conducted on 80 postpartum women who referred to healthcare centers of Mashhad, Iran, 2016, and randomly selected by multistage cluster sampling method. The subjects were placed in two groups of control and intervention (n=40 for each group). The intervention group received three 80-min theoretical and practical training sessions based on the health literacy strategies, while the control group received the routine care. Data was collected using Short Test of Functional Health Literacy in Adults (S-TOFHLA), Rapid Estimate of Adult Literacy in Medicine (REALM), and International Physical Activity Questionnaire (IPAQ) before and eight weeks after training. Data analysis was performed using the chi-square, independent and paired t-tests with SPSS software version 16. Results: There was no significant difference between the levels of health literacy and physical activity among the groups before intervention; however, eight weeks after the educational intervention, the levels of both health literacy and physical activity significantly increased among the intervention group (P